Probiotics as Alternative Therapy for Psychometric Disorders in Hepatic Encephalopathy - Bany Faris Amin; Irfan Kresnadi; Vannessa Karenina; GM Yudi Prasetia A; Trivani Putri; Juferdy Kurniawan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2019)
Aim: To identify whether probiotics have the same effectiveness as lactulose in improving the results of psychometric testing in patients with hepatic encephalopathy.Method: Literature Searching were performed on Pubmed, EBSCOhost, Scopus, and Cochrane databases to obtain an randomized controlled trial (RCT) or a systematic review. Searches were made with the keywords "hepatic encephalopathy", "probiotic", "lactulose" and number connection test  ("NCT").  Search is continued by excluding the literature through abstract and full text.Results: Two studies were found to be relevant according to the criteria. The study by Mittal showed that probiotics were better than lactulose in improving NCT-B with a risk ratio (RR) of 0.88 (95% CI: 0.54-1.44; p = 0.62) but not better for improving NCT- A with RR 1.43 (95% CI: 0.62-3.24; p = 0.40). In the Sharma study, lactulose was better in improving NCT score with the mean difference (MD) 6.7 (95% CI: 0.58-12.82) and in the Li study, there was no significant significance between MD 3.93 (95% CI: -0,72-8,58)Conclusion: In conclusion, Probiotics cannot replace lactulose as a standard therapy for hepatic encephalopathy. There is not enough evidence that proves probiotics are better than lactulose.